2005
DOI: 10.1002/ar.a.20190
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic distribution of immunoreaction for estrogen receptor alpha in rat ameloblasts

Abstract: Estrogen has a diverse function, including cell proliferation and differentiation via estrogen receptors (ER), which have been reported to be the case in various tissues in addition to female reproductive organs. A recent immunocytochemical study has reported the expression of ER␣, a subtype of ER, in rat odontoblasts, suggesting an involvement of estrogen in the differentiation of tooth-forming cells. However, there is no information on the ER␣ immunoexpression in ameloblasts. The present study was therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 45 publications
0
24
0
1
Order By: Relevance
“…We identified ESR1 as the highest priority candidate gene within the region using Endeavour. It has been reported that expression of oestrogen receptor α occurs during the differentiation of tooth-forming cells 36. Previous studies have shown that the oestrogen receptor acts as a transcriptional corepressor for Smad3 (Sma and MAD-related protein 3), which is one of the major intracellular transducers of transforming growth factor-β (TGF-β) signalling 37 38.…”
Section: Discussionmentioning
confidence: 99%
“…We identified ESR1 as the highest priority candidate gene within the region using Endeavour. It has been reported that expression of oestrogen receptor α occurs during the differentiation of tooth-forming cells 36. Previous studies have shown that the oestrogen receptor acts as a transcriptional corepressor for Smad3 (Sma and MAD-related protein 3), which is one of the major intracellular transducers of transforming growth factor-β (TGF-β) signalling 37 38.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Similar models have shown growth hormone deficiency as associated with caries resistance. 13 More recent studies have demonstrated that the receptors of these hormones are expressed during amelogenesis, and ERα [14][15][16] and GHR have been identified in enamel formation in rats. 17 Therefore, it is possible that genetic variations in ESR1, which is the gene that codifies ERα, and in GHR are involved in caries susceptibility and developmental defects of enamel (DDE).…”
Section: Introductionmentioning
confidence: 99%
“…Further research has shown that Hsp25 might be directly upregulated by estrogen because of estrogen responsive element in the 5′ promoter region of this gene [35]. Recent studies suggested that the ERα immunoreactions were exhibited both in odontoblasts and ameloblasts, suggesting toothforming cells as targets for estrogen action [25,36,37]. Enamel discoloration and defect are major clinical manifestations of DF.…”
Section: Discussionmentioning
confidence: 98%
“…The results suggested that ESR gene polymorphism might be associated with acquisition of peak bone mass, in particular trabecular bone. Enamel, which is derived from the ectoderm, undergoes matrix formation and subsequent maturation to become the hardest tissue in mammals [25]. Ohshima et al demonstrated transient expression of 25-kDa heatshock protein (Hsp25) during rat amelogenesis, suggesting that this protein is involved in the differentiation of ameloblasts in animal experiment [34].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation